Challenges and Opportunities Encountered by the Master of Arts in Educa-tion (MAED) Students in Cotabato City - Dangalao, Tong Kabenbelan (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to determine the needs and problems in conducting research among the MAED students of Higher Education Institutions in Cotabato City Graduate Schools. It utilized the descriptive–quantitative type of research, and it was conducted in the selected college and universities-graduate schools in Cotabato City. The study's respondents were the forty-four (44) Master of Arts in Education graduating students for 2015-2016. The study employed total enumeration as a sampling technique. A survey questionnaire was generated upon reviewing the related literature and other secondary sources such as research articles and journals. The study's statistical tools used frequency and percentage counts, mean, and the grand mean. The needs of the MAED students in conducting research were perceived as "needed," while the level of difficulties encountered by the MAED students was perceived as "difficult." Financial aspects were seen as a hindrance to their research work. Likewise, a school offering graduate college in the city has equipped a library to give students access to the research materials they need. Similarly, there is still a need to develop the student's skills in conducting research. Students conducting research were it hard to manage their time while most of them were married and at the same time working. It is recommended that research subjects be emphasized to students taking research courses. There should be an organized schedule for students to consult closely with their adviser. The graduate studies program in the city should strengthen its research program.